Correlation of Rhinomanometry Measurement and True Lateral Radiography towards the Degree of Upper Airway Obstruction in Patients with Adenoid Hypertrophy - Nanda Mayasari; Sutji Pratiwi Rahardjo; Abdul Kadir; Muhammad Fajar Perkasa; Abdul Qadar Punagi (Faculty of Medicine, Hasanuddin University., 2021)
Background: Adenoid hypertrophy is one of the most common disorders in children which may lead to upper airway obstruction. Various modalities to measure airway obstruction in patients with adenoid hypertrophy, including true lateral radiographs, nasoendoscopy, and rhinomanometry are available; however, the results from different studies are still controversial. This study aimed to determine the relationship between the results of rhinomanometry and the true lateral radiographs to the degree of upper airway obstruction in patients with adenoid hypertrophy. Methods: This cross-sectional study included a total of 33 patients with adenoid hypertrophy aged 5-18 years using a purposive sampling technique. Patients diagnosed with adenoid hypertrophy were subjected to a true lateral examination using lateral neck radiographs to measure the degree of airway obstruction. Subsequently, an active anterior rhinomanometry was performed by measuring resistance and nasal airflow and then measuring the degree of airway obstruction. Data analysis was done using Chi-Square test. Results: The rhinomanometric nasal resistance in the inspiratory phase was 0.4159 ± 0.15201 Pa/cm3/s and 0.3694 ± 0.13717 Pa/cm3/s in the expiration phase. The results showed a significant relationship between the true lateral radiographs and both nasal inspiratory (p=0.005) and expiratory resistance (p=0.004). Similarly, the relationship between the true lateral radiographs and nasal airflow on both inspiratory and expiratory rhinomanometry was significant (p<0.05). Conclusion: Rhinomanometric measurements can be used as an additional objective examination in assessing the degree of upper airway obstruction in patients with adenoid hypertrophy prior to surgery.